Power Sharing and Zoning Formula for Managing Nigeria's Diversity - Sule, Babayo; Sambo, Usman (University of Jember, 2022)
Nigeria is composed of plural and multi-complex societies with multiple ethnic groups of up to 500 cultural diversities. This country surmounts the obstacles of managing diversity through an informal setting popularly identified as a zoning formula and power sharing among the federating units. The pattern and trend in which the practice maintains Nigeria's diversity is a good lesson for a study of plural societies and consociationalism. The study aimed to examine the nature and dimension of zoning formula and power sharing in Nigeria and analyze how the strategies of zoning formula and power sharing helped manage diversity in Nigeria. The study was identified as a descriptive qualitative method that sought to describe Nigeria's strategy for managing diversity. The study uncovered that power sharing and zoning consist of constitutional and unconstitutional ones, with the former supported by legal provisions. Simultaneously, the latter is designed based on principles and gentleman agreements. The study recommended that constitutional provisions should never be sacrificed on the altar of the personal elite agreement. Instead, sharing power through zoning should be retained to prevent suicide for credibility and competency. It is a plausible shock absorber that will continue to sustain Nigerian federalism, and other plural societies can borrow this model as a political means of resolving diversities.Keywords: Consociationalism, Constitution, Nigeria.